Academic Self Concept and Academic Achievement of Indian CBSE School Students - R. Gayatri Iyengar; G. Padma Gouri; Mahendra Kumar; Yanjana (Medsci Publications, 2021)
Introduction: Student's self-concept about their academic capabilities plays an important role in academic achievement. Main objective of the study was to examine the relationship between academic self-concept and academic achievement. Methods: The sample (Male 261, Female 320, aged 17-19 years) were drawn from 15 secondary schools affiliated with CBSE board, India. Academic achievement was measured by self-reported CGPA of the previous year. Academic self-concept was measured by Kample and Naik Academic Self Concept Scale (ASCS). Data obtained was analyzed with the help of SPSS (16th, version) and JASP (Version 0.14.1). Results: Measurement model for ASCS was excellent fit in the samples [GFI=9971, CFI=.926, TLI=.897, RMSEA=1173(90%CI: Lower-0.1019: Upper-0.1333) and SRMR=0.0445].The result of the study revealed that there was a positive relationship between academic self-concept and academic achievement(r=117) and this relationship was stronger for male students (r=0.125) than that of female students (r = .091). Academic self-concept accounted for 12.5% of the variance in the academic achievement. Moreover, gender differences in the academic self-concept of the students were also found (P= 0.01). Conclusions: This finding suggests that students performed academically better when they had good level of academic self-concept. Female students had significantly higher academic self-concept than male students.